2012
DOI: 10.1111/j.1398-9995.2012.02884.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Bordetella pertussis BPZE1 protects against allergic airway inflammation and contact dermatitis in mouse models

Abstract: Our study demonstrates the broad anti-inflammatory properties of the attenuated B. pertussis BPZE1 vaccine candidate and supports its development as a promising agent to prevent and/or treat allergic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…It is now well established that exposure to microorganisms is an important factor in shaping the immune system and also is important for the susceptibility to develop allergies and asthma (26). This holds true for the exposure to exogenous bacteria, and different research groups have shown that exposure to bacteria prior to or starting at the time of sensitization reduces the development of allergic disease in various models (27)(28)(29)(30). There is also increasing evidence that microbiota contribute to the susceptibility to develop an allergic disease, and changes in the composition of the microbiota have been linked to the increased prevalence of allergies and asthma (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that exposure to microorganisms is an important factor in shaping the immune system and also is important for the susceptibility to develop allergies and asthma (26). This holds true for the exposure to exogenous bacteria, and different research groups have shown that exposure to bacteria prior to or starting at the time of sensitization reduces the development of allergic disease in various models (27)(28)(29)(30). There is also increasing evidence that microbiota contribute to the susceptibility to develop an allergic disease, and changes in the composition of the microbiota have been linked to the increased prevalence of allergies and asthma (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The use of an attenuated B. pertussis strain administered intranasally has been successfully tested in animal models and moved to Phase I clinical trials. 39,40 Although this is a promising application that has shown some advantages, 41,42 it shares the potential safety concerns related to the use of attenuated pathogens. 39 An interesting alternative that combines some of the above-mentioned strategies is the use of outer membrane vesicles, also called nanoparticles, which contain bacterial surface antigens.…”
Section: Development Of Improved Pertussis Vaccinementioning
confidence: 99%
“…Mice were euthanized 48 h after the last aerosolized OVA challenge (day 26), and bronchoalveolar lavage fluids (BALFs) were collected as previously reported method [68]. Briefly, after euthanasia, tracheotomy was carried out and an arteriovenous indwelling needle (20G; BRAUN, Germany) was inserted .…”
Section: Bronchoalveolar Lavage Collection and Cell Countingmentioning
confidence: 99%